AN INVESTIGATION OF ANIMAL SPECIES TRADE AT PET SHOPS OF RAWALPINDI AND MULTAN CITIES - T. Mahmood; S. M. A. Shah; M. Rais; M. S. Nadeem (Journal of Animal and Plant Sciences, 2011)
The current study aimed to collect information about the trade of animal species in two selected markets; Goodri market, Multan and College Road market, Rawalpindi during December, 2009 to June 2010. Data were collected by using primary and secondary methods. The results revealed that three major groups of animals (reptiles, birds and mammals) were being sold in Multan market; birds constituted 76.22% (maximum) by number, mammals 7.82%, fish 11.45% and reptiles 4.51% (minimum). Whereas, in Rawalpindi market, birds constituted 85% (maximum) followed by fish (5.75%), mammals (5.18%) and reptiles (4.05%). A comparison of the two markets revealed noticeable differences between numbers of animals being traded viz. 760 birds, 78 mammals, 114 fish and 45 reptiles in Multan market versus 901 birds, 55 mammals, 61 fishes and 43 reptiles in the Rawalpindi market. Average prices of animals were found comparatively different in the two markets; generally lower sale prices were recorded in Multan. Maximum revenue was generated from the trade of various bird species. Regression analysis between volume of trade (VOT) and other variables showed that an increase in average sale price of animal species caused a decrease in Volume of Trade (VOT) of the market.
Keywords: Animal trade; major species; birds; mammals; reptiles; Pakistan.